2015
DOI: 10.21767/2471-805x.100003
|View full text |Cite
|
Sign up to set email alerts
|

Mauriac Syndrome in the Age of Newer Insulin Analogues

Abstract: The authors describe a five year-old plump looking female child with poorly controlled type 1 diabetes mellitus, hepatomegaly and growth retardation. Contrary to the usual phenotype of thin emaciated appearance in type 1 diabetes mellitus, the presence of above features should make one suspect Mauriac syndrome. Since the basis of this syndrome is poor metabolic control, early recognition is important. The authors emphasize the importance of optimal glycaemic control in preventing complications associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Isolated patients with this syndrome are still being reported. 3 , 7 – 10 The pathophysiology of this entity has not been elucidated. High index of suspicion for this syndrome should be maintained in a poorly controlled diabetic child with delayed growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated patients with this syndrome are still being reported. 3 , 7 – 10 The pathophysiology of this entity has not been elucidated. High index of suspicion for this syndrome should be maintained in a poorly controlled diabetic child with delayed growth.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of the metabolic control in children with Mauriac syndrome is mandatory and includes treatment with insulin analogues; 8 however, if it is introduced too fast, retinopathy can be induced or existing retinopathy and/or nephropathy can be aggravated within months. 5 , 6…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recent advances in pathology and imaging, glycogen hepatopathy is only diagnosed by liver biopsy [5,6]. It is worth mentioning that synthetic liver functions are not affected in glycogen hepatopathy which could narrow the differential diagnosis [7]. A recent small case series found that elevated levels of lactic acid appeared to be a part of the disease process [8].…”
Section: Discussionmentioning
confidence: 99%